Peran sirkumsisi sebagai pencegahan infeksi herpes genetalis: suatu studi kohort retrospektif - Made Wardhana; Martina Windari; Marrietta Sugiarti Sadeli; Anak Agung Gde Putra Wiraguna; Ni Made Dwi Puspawati; I Gusti Ayu Agung Elis Indira; Pande Agung Mahariski (DiscoverSys Inc., 2021)
Background: Recurrent genital herpes (RGH) is a sexually transmitted infection that is a serious public health problem and is quite prominent in most countries worldwide. Management for this infection is antiviral and circumcision. Male circumcision significantly reduces human immunodeficiency virus (HIV) infection and other sexually transmitted infections. This research aims to evaluate circumcision efficacy as the prevention for herpes simplex virus type 2 (HSV-2) infection compared with oral acyclovir.Methods: This research is an experimental study with a retrospective cohort approach. We included 45 males, 24 subjects circumcised and 21 subjects without circumcision and took oral acyclovir as standard treatment. RGH was diagnosed based on typical clinical manifestation. Follow up treatment every two weeks and continued to 2 months after circumcised and given with oral acyclovir. Successful treatment was stated without recurrent genital herpes.Results: Of 24 circumcised subjects, 19 were cured, and five non-circumcised subjects suffered recurrent genital herpes (not cured). Among 21 subjects without circumcision was cured, and 12 subjects were not cured. Based on these results, the value of NNT= 2.7.Conclusion: Circumcision can be considered effective in reducing the incidence of HGR and prevent recurrence of HGR with the NNT value of 2.7. Latar Belakang: Herpes genetalis rekuren (HGR) merupakan infeksi menular seksual menjadi masalah kesehatan masyarakat yang serius dan cukup menonjol pada sebagian besar negara di dunia. Penanganannya adalah oral dengan antivirus dan tindakan sirkumsisi. Sirkumsisi pada pria secara signifikan mengurangi insiden infeksi human immunodeficiency virus (HIV) dan penyakit infeksi menular lainnya. Penelitian ini mengevaluasi efikasi sirkumsisi sebagai pencegahan infeksi virus herpes simpleks tipe 2 (HSV-2) dibandingkan dengan pemberian obat asiklovir.Metode: Studi ekperimental dengan pendekatan retrospektif kohort dengan mengikutsertakan 45 subjek pria dewasa, 24 subjek disirkumsisi dan 21 tanpa sirkumsisi dan hanya diberikan asiklovir sebagai obat standar. Diagnosis HGR dilakukan secara klinis dengan yang manifestasi klinis yang khas da pemeriksaan Tzanck. Setelah pemberian terapi dilakukan kontrol setiap 2 minggu sampai 2 bulan. Terapi dinyatakan berhasil bila tidak ada kekambuhan.Hasil: Dari 24 subjek disirkumsisi, 19 subjek dinyatakan sembuh dan 5 subjek mengalami kekambuhan (tidak sembuh). Dari 21 subjek tanpa sirkumsisi, 9 subjek dinyatakan sembuh dan 12 subjek dinyatakan tidak sembuh. Berdasarkan hasil ini didapatkan nilai NNT=2,7.Simpulan: Sirkumsisi dapat dinilai cukup efektif mengurangi angka kejadian HGR dan dapat mencegah kekambuhan HGR dengan nilai NNT 2.7.